A novel adsorbent formed from blast furnace slag by alkali fusion for phosphate ions removal / Takaaki Wajima - Wajima, Takaaki (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Blast furnace slag (BF slag) was converted using alkali fusion method into a novel adsorbent to remove phosphate from aqueous solutions. The slag was mixed with NaOH powder (NaOH / Slag = 1.6) and then heated at 600 °C for 6 h to prepare the fused precursor. The precursor was stirred in distilled water at room temperature to synthesize the adsorbent and its ability to remove phosphate from aqueous solution was investigated. Fand PO43- removal efficiencies by the adsorbent were higher than those of raw BF slag, with the removal of PO43- being particularly excellent (99%), while Cl-, SO42-, NO3- and Brwere barely adsorbed. With increasing pH of the solution to around pH 7, phosphate removal of the product increases, and then becomes almost constant. The equilibrium adsorption capacity of the product for PO43- was found to fit the Freundlich isotherm better than the Langmuir isotherm, and the calculated maximum PO43- adsorption capacity of the product was 7.67 mmol/g. Phosphate removal corresponded better to a pseudo second-order kinetic model than a pseudo first-order model. The high affinity of the adsorbent for PO43- in aqueous solution was caused by the formation of hydroxyapatite [Ca5(PO4)3(OH)] and brushite [CaHPO4•2H2O]